LOGIKA FUZZY UNTUK MENENTUKAN ASUPAN KALORI PADA TERAPI DIET TERHADAP PENDERITA OBESITAS - Maha Rani (Jurnal Inovasi Teknik Informatika, 2018)
It takes time for a while to determine calory intake for diabetics. Computer technology has been growing rapidly, that can help human life even outside the field of computer science. One of the ways to fulfill those needs is by using fuzzy methode. Fuzzy methode has been applicated in many fields, especially in health. In diet theraphy, obesity can be prevented by restriction in food intake, called diet. Calory intake is determined manually by counting ideal weight combined with other weight. In this research, researcher use fuzzy logic to determine calory intake for patients with obesity when nutrition section still use counting ideal weight, basal needs and activity manually. Therefore, it is a need a methode that can determine calory intake in diet therapy for the sake of a new knowledge and more competitive like for Puskesmas Ambacang.Keywords : Fuzzy Logic, Mamdani Method, Calory Intak